Global Cultures | African Culture - Catherine Chambers (Oxford, United Kingdom Capstone Global Library Ltd, 2013)
African Culture covers a vast array of subjects on African culture -- from fine arts to ceremonies, from legends to the culture's global influence.
Keywords: Non Fiction